Modeling of some nonstationary processes in tokamak plasmas - Borisov, M.A.; Cherkasov, S.V.; Danilov, A.V.; Dnestrovskij, Yu.N.; Dnestrovskij, A.Yu.; Field, A.; Lysenko, S.E.; Meyer, H.; Vershkov, V.A. (Вопросы атомной науки и техники, 2013)
The results of modeling of shots from two series of experiments in two tokamaks with rather different geometric parameters are presented. The first one includes two shots from the spherical tokamak MAST with current ramp up, and the second one, a number of T-10 shots with periodic gas puffing. The modeling was performed with the ASTRA code in the framework of Canonical Profiles Transport Model (CPTM). Представлены результаты моделирования импульсов из двух серий экспериментов на двух разных токамаках, существенно отличающихся геометрическими параметрами. Первая серия включает два импульса с нарастанием тока сферического токамака MAST, а вторая – несколько импульсов Т-10 с периодическим газонапуском. Моделирование осуществлялось с помощью кода ASTRA в рамках транспортной модели канонических профилей (ТМКП). Представлені результати моделювання імпульсів з двох серій експериментів на двох різних токамаках, що істотно відрізняються геометричними параметрами. Перша серія включає два імпульси з наростанням струму сферичного токамака МАST, а друга – декілька імпульсів Т-10 з періодичним газонапуском. Моделювання здійснювалося за допомогою коду ASTRA в рамках транспортної моделі канонічних профілів (ТМКП).